2001
DOI: 10.1073/pnas.141118798
|View full text |Cite|
|
Sign up to set email alerts
|

Role of a pineal cAMP-operated arylalkylamine N- acetyltransferase/14-3-3-binding switch in melatonin synthesis

Abstract: The daily rhythm in melatonin levels is controlled by cAMP through actions on the penultimate enzyme in melatonin synthesis, arylalkylamine N -acetyltransferase (AANAT; serotonin N -acetyltransferase, EC 2.3.1.87 ). Results presented here describe a regulatory/binding sequence in AANAT that encodes a cAMP-operated binding switch through which cAMP-regulated protein kinase-catalyzed phosphorylation [RRHTLPAN → RRHpTLPAN] promotes formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
200
1
18

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 181 publications
(227 citation statements)
references
References 22 publications
8
200
1
18
Order By: Relevance
“…Previously, the available evidence indicated only that light-evoked physiological changes in AANAT activity in retina and pineal were attributable to protein degradation (Gastel et al, 1998;Schomerus et al, 2000;Zatz et al, 2000;Falcon et al, 2001;Iuvone et al, 2002). A physiological effect of 14-3-3 binding on the K m of AANAT for amine substrates was inferred based on studies using expressed protiens Ganguly et al, 2001Ganguly et al, , 2005. The current results provide new insight on a mechanism whereby light can rapidly downregulate melatonin synthesis.…”
Section: Discussionmentioning
confidence: 72%
“…Previously, the available evidence indicated only that light-evoked physiological changes in AANAT activity in retina and pineal were attributable to protein degradation (Gastel et al, 1998;Schomerus et al, 2000;Zatz et al, 2000;Falcon et al, 2001;Iuvone et al, 2002). A physiological effect of 14-3-3 binding on the K m of AANAT for amine substrates was inferred based on studies using expressed protiens Ganguly et al, 2001Ganguly et al, , 2005. The current results provide new insight on a mechanism whereby light can rapidly downregulate melatonin synthesis.…”
Section: Discussionmentioning
confidence: 72%
“…The pulldown of CAT with 19c⌬T is reminiscent of the copurification of 14-3-3 proteins with serotonin N-acetyltransferase. 14-3-3 protein interacts with serotonin N-acetyltransferase in a phosphorylation dependent manner (47,48). Interestingly, our results showed that recombinant CAT was purified as a phosphorylated protein and readily formed a complex with 19c⌬T and its functionally active mutant 19cFHA in vitro.…”
Section: Discussionmentioning
confidence: 72%
“…2). Phosphorylation of these sites promotes binding to 14-3-3 proteins, which reduces the Km for the arylalkylamine substrates and also protects the enzyme from proteasomal proteolysis (Ganguly et al, 2001a;Obsil et al, 2001;Ganguly et al, 2005). In addition, a highly conserved lysine in the N-terminal region, may mediate proteasomal proteolysis Klein et al, 1997).…”
Section: Introductionmentioning
confidence: 99%